Dactylosporangium tropicum sp. nov., isolated from soil - Chitti Thawai; Somboon Tanasupawat; Takuji Kudo (My University, 2010)
Two novel actinomycete strains, designated KB2-4(T) and KB9-2, were isolated from soil samples. Both isolates formed finger-shaped sporangia on short sporangiophores that emerged directly from substrate hyphae. The cell-wall peptidoglycan contained glutamic acid, glycine, alanine and meso-diaminopimelic acid; the whole-cell sugars were galactose, glucose, mannose, rhamnose, ribose and xylose. The diagnostic phospholipid was phosphatidylethanolamine. The predominant menaquinones were MK-9(H(8)) and MK-9(H(6)). Mycolic acids were not detected. The predominant cellular fatty acids (>20 %) were iso-C(16 : 0) and anteiso-C(17 : 0). For both strains, the G+C content of the genomic DNA was about 72 mol%. The morphological and chemotaxonomic characteristics of the two strains were typical of members of the genus Dactylosporangium. Phylogenetic analysis using 16S rRNA gene sequences also indicated that these strains should be classified in the genus Dactylosporangium and showed that the closest relative was Dactylosporangium salmoneum NRRL B-16294(T) (99.1 % 16S rRNA gene sequence similarity). DNA-DNA relatedness and some physiological and biochemical properties indicated that the isolates could be readily distinguished from their closest phylogenetic relatives. On the basis of these phenotypic and genotypic data, the isolates represent a novel species, for which the name Dactylosporangium tropicum sp. nov. is proposed. The type strain is strain KB2-4(T) ( = BCC 34760(T) = JCM 15673(T)).
Keywords: Plant Pathogens and Fungal Diseases